The Prevalence and Indications for Caesarean Section at Kitwe Teaching Hospital in 2018 - Kamanda, Fines B.; Malama, Angel (International Research in Medical and Health Sciences, 2021)
Introduction: Worldwide, there has been an increase in the prevalence of Caesarean sections. Zambia has a national prevalence of 7.2%, however, in its two major referral Hospitals, the University Teaching Hospital (UTH) and Ndola Teaching Hospital (NTH) the prevalences were 18% and 20% respectively which are above the recommended 10 to 15%. The prevalence and indications for caesarean sections at Kitwe Teaching Hospital (KTH) can be used to make an indication monitoring criteria to reduce foetal and maternal death. Objective: To determine the prevalence and indications for caesarean sections at Kitwe Teaching Hospital from January to December of 2018 and define their demographics. Methodology: An analytical Cross-sectional, hospital-based retrospective study was conducted at Kitwe Teaching Hospital (KTH) to determine the prevalence and indications of caesarean sections. Randomly sampled information was collected, entered, and analysed with the statistical package for social sciences (SPSS) and Microsoft Excel 2013. Results: The prevalence of caesarean sections was 37.5% and the most common indications where foetal distress (20.6%), cephalopelvic disproportion (19.8%), prolonged labour (14.9%), previous caesarean section (14.6%), and psychosis as the least (0.3%). Conclusion: The prevalence was higher than recommended by World Health Organisation even if it is comparable to other referral hospitals in sub-Saharan African, American, and Asia. It needs to be lowered because there is a correlation of C-sections near 10% with a reduction of maternal and neonatal mortality. The most common indication was Foetal distress followed by cephalopelvic disproportion, prolonged labour, and previous where which require proper monitoring and audit to avoid speculative diagnosis.